Functional Potential and Chemical Profile Analysis of Propolis Oil Extracted from Propolis of Balochistan. (20th May 2022) - Aziz, Saliha; Akbar, Ali; Gul, Zareen; Sadiq, Muhammad Bilal; Achakzai, Jahangir Khan; Khan, Nazir Ahmad; Samad, Abdul; Rehman, Zia Ur; Ali, Imran
Abstract : Propolis oil (PO) was examined for chemical composition, phenolic and flavonoid content, and antioxidant and antimicrobial potential. Phenolic and flavonoid contents were 2.388 ± 1.116 mg GAE/g and 0.579 ± 0.140 mg QE/g. Oil showed 64.59 ± 14.59% inhibition of DPPH radical and significant antibacterial activities against target bacteria. Salmonella typhi was found to be highly sensitive (27.23 ± 4.35 mm) to PO, compared to Escherichia coli (23.40 ± 3.21), Staphylococcus aureus (21.43 ± 2.80), and Klebsiella pneumoniae (21.26 ± 3.25). The MIC and MBS values of PO were 0.35 and 0.7 mg/mL for S. typhi and E. coli, whereas they were 0.7 and 1.4 mg/mL for S. aureus . Moreover, the PO was found to be bacteriostatic for K. pneumoniae . Aspergillus flavus was found to be highly sensitive to PO, with an effective growth inhibition percentage of 73%, followed by Aspergillus niger (70%), whereas Aspergillus parasiticus was less sensitive with 25% growth inhibition. Functional groups in PO were determined with an FTIR spectrophotometer, and alcohol, alkane, aldehydes, alkenes, and ketones groups were found to be present, whereas GC-MS analysis revealed the presence of 27 different medicinal compounds, among which α -copanene (29.85%), benzyl benzoate (26.8%), 2, 4-bis[1-(4-hydroxyphenyl)isopropyl]phenol, acetophenone (14.92%), undecylenic aldehyde (7.46%), p-linalool (5.9%), and ethyl 3-phenylpropionate (4.47%) were found in abundance.